2018
DOI: 10.1007/s11910-018-0816-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of Acute and Chronic Sinusitis

Abstract: Recent studies have shown improvement in both the mortality and the morbidity associated with the neurologic complications of acute and chronic sinusitis. However, there are still a large portion of patients with long-term sequelae, and the literature reports a morbidity rate of approximately 30%. The most common post-treatment morbidities include permanent changes in vision, seizures, and hemiparesis. Although the overall incidence of neurologic complications from a sinogenic source are rare, the potential lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 35 publications
2
38
1
9
Order By: Relevance
“…Several studies have shown that sinusitis-induced intracranial abscesses occur more commonly among adolescents and young adults in their 20s and 30s. 3,12,17,18 Our results are inconsistent with those of previous studies; we found that abscesses occur at any age, although the reason remains unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that sinusitis-induced intracranial abscesses occur more commonly among adolescents and young adults in their 20s and 30s. 3,12,17,18 Our results are inconsistent with those of previous studies; we found that abscesses occur at any age, although the reason remains unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Direct extension via osteomyelitis of the sinus walls or bony defects (congenital or posttraumatic) is uncommon. 6,18 Thus, the effect of drainage from the sinus may be limited. The present study showed no significant benefit of ESS in terms of reducing in-hospital mortality, blood transfusion, readmission, revision neurosurgery, or length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic infections of the frontal sinus are difficult to treat and may lead to serious complications. Given the close anatomical relationship of the frontal sinus to the orbit and anterior cranial base, infection may spread intracranially via foramina of Breschet or posterior table violation leading to meningitis, venous sinus thrombosis, orbital infection, subperiosteal abscess (i.e., Pott's puffy tumor), and brain abscess . Osteomyelitis of the frontal bone can lead to resistant infection and unsalvageable bone.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection of the frontal sinus poses a challenging clinical problem. Unresolved infection can lead to serious orbital or intracranial complications given the proximity of the frontal sinus to these structures . Furthermore, chronic infection may lead to osteomyelitis of fragmented, devitalized bone, which may be unsalvageable …”
Section: Introductionmentioning
confidence: 99%